2020
DOI: 10.1038/s41467-020-16237-1
|View full text |Cite
|
Sign up to set email alerts
|

In-situ structure and catalytic mechanism of NiFe and CoFe layered double hydroxides during oxygen evolution

Abstract: NiFe and CoFe (MFe) layered double hydroxides (LDHs) are among the most active electrocatalysts for the alkaline oxygen evolution reaction (OER). Herein, we combine electrochemical measurements, operando X-ray scattering and absorption spectroscopy, and density functional theory (DFT) calculations to elucidate the catalytically active phase, reaction center and the OER mechanism. We provide the first direct atomic-scale evidence that, under applied anodic potentials, MFe LDHs oxidize from as-prepared α-phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
594
2
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 702 publications
(690 citation statements)
references
References 76 publications
27
594
2
6
Order By: Relevance
“…32,153 It is established that Fe incorporation plays a critical role for boosting the OER activity, especially in Ni-and Co-based electrocatalysts, because of the enhanced the density of active sites and rapid OH − adsorption and O 2 desorption during the OER process. [153][154][155] For example, Fe-doped NiSe/NF, Ni 3 S 2 /NF, and LaNiO 3 displayed higher OER activity in comparison with pristine materials. 151,156,157 Similarly, introducing Ni and Co cations into the host materials is also beneficial for improving the catalytic performance owing to the preferable reaction kinetics.…”
Section: Cation Dopingmentioning
confidence: 99%
“…32,153 It is established that Fe incorporation plays a critical role for boosting the OER activity, especially in Ni-and Co-based electrocatalysts, because of the enhanced the density of active sites and rapid OH − adsorption and O 2 desorption during the OER process. [153][154][155] For example, Fe-doped NiSe/NF, Ni 3 S 2 /NF, and LaNiO 3 displayed higher OER activity in comparison with pristine materials. 151,156,157 Similarly, introducing Ni and Co cations into the host materials is also beneficial for improving the catalytic performance owing to the preferable reaction kinetics.…”
Section: Cation Dopingmentioning
confidence: 99%
“…For example, Wang et al prepared graphene-like C 3 N 4 materials with high surface area (various edge and wrinkled structures) for a Zn-air battery, and reported a peak density up to 100 mW cm −2 . [174] By taking advantage of the ORR and OER of various 2D materials (e.g., LDHs and MOF materials), [175][176][177][178][179][180] along with the above discussed geometric point defects and edge-like structures, design of high-performance energy storage devices based on the promising catalysis can be highly expectable.…”
Section: Geometric Point Defects and Edge-like Structuresmentioning
confidence: 99%
“…Although the structures and chemical compositions of many LDHs are complex, recent investigations on several LDHs by Strasser et al confirmed the critical role of chemical doping in regulating the catalysis. [175][176][177] It was found that additions of Fe species into Co and Ni based LDHs enhanced the OER activity significantly. [176,177] More recently, Strasser et al further investigated the relationship between the structure and catalytic mechanism of NiFe and CoFe LDHs (both have high activity on OER) at the atomic level.…”
Section: Chemical Doping and Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike those amorphous (oxyhyr)oxides, crystalline CoNi-FeOOH is evidenced in the post-OER CoNi-Fe 3 N, which confirms that CoNi co-incorporation is favorable for the orderly rearrangement of Fe atoms in Fe 3 N toward FeOOH. More importantly, compared with the common Fe/Co/Ni layered double hydroxides (LDH) [51] and oxides, [52] which can also undergo reconstruction during OER, the metallic CoNi-Fe 3 N can ensure the electronic conductivity for generated CoNi-FeOOH, which is highly important for efficient electrocatalysis.…”
Section: Insights Into Oer-conditioned Catalystsmentioning
confidence: 99%